1977
DOI: 10.1007/bf01964880
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and study of functional mast cells from lung and mesentery of the guinea pig

Abstract: A method is described for the dissociation of guinea pig lung and mesentery into their component cells. The method comprises incubation of the tissues with the enzyme pronase in Ca++- and Mg++-free saline followed by mechanical dispersion and yields on average 3-8% free mast cells. These cells are morphologically intact and viable. They retain an active sensitization or can be passively sensitized. The levels of cAMP and cGMP in the whole cell suspension respond to catecholamine, histamine or cholinergic stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…These differences are in agreement with functional studies showing that the mast cell populations iso lated from the guinea pig and rat lung have different properties [10,11,[22][23][24].…”
Section: Discussionsupporting
confidence: 81%
“…These differences are in agreement with functional studies showing that the mast cell populations iso lated from the guinea pig and rat lung have different properties [10,11,[22][23][24].…”
Section: Discussionsupporting
confidence: 81%
“…Numerous recent studies deal with the mea surement of released mediators, but some of these products are not representative of mast cell activity only and, moreover, in vitro studies with passively sensitized tissues which are usually performed are far from representative of physiological conditions [12,13]. The present study revealed the mast cell reactivity in vivo, during sensitization and challenge.…”
Section: Discussionmentioning
confidence: 52%
“…(9). The role of mast cells on the 8-day PCA in guinea pigs has also been considered to be the same as that on the IgE-mediated PCA in rats (24). All these findings taken together suggest that the mode of the inhibitory action of AA-344 on the 8-day PCA in guinea pigs was the same as that on the 72-hr PCA in rats.…”
Section: Discussionmentioning
confidence: 86%